Nutritional awareness among the participants of national nutritional anaemia prophylaxis programme - Bhuvaneshwari P (Department of Home Science, College of Agriculture, 2007)
Iron deficiency anaemia is a major global nutritional problem and is prevalent in 50-80 per cent of population in different parts of India. Towards reducing anaemia, the government of India (GOI) launched the National Nutritional Anaemia Prophylaxis Programme (NNAPP) in 1970.National Anaemia control and Prophylaxis Programme has been fighting the relentless struggle to control the ailment since 1970, but has not yielded much. Hence a study entitled “Nutritional awareness among the participants of NNAPP” was undertaken to elicit the existing knowledge, attitude and practice on the programme among the participants identify the lacunae and to suggest correct preventive measures among the participants and to study its impact through KAP studies.